N/S co-doped coal-based porous carbon spheres as electrode materials for high performance supercapacitors. Issue 19 (17th March 2020) - Lv, Yan; Chen, Jingjing; Jia, Wei; Wu, Xueyan; Guo, Jixi; Ding, Lili; Jia, Dianzeng; Tong, Fenglian
Abstract : N/S co-doped porous carbon spheres were prepared using one step strategy for high performance supercapacitors. Abstract : N/S co-doped porous carbon spheres (NSPCSs) were prepared by a simple ultrasonic spray pyrolysis (USP) using the mixed solution of coal oxide and l -cysteine, and without a subsequent activation process. The surface properties of carbon materials have been successfully modified by the concurrent incorporation of N and S. So the capacitive performance of NSPCSs was greatly enhanced. It is used as a supercapacitor electrode to achieve a high specific capacitance of 308 F g −1 at a current density of 1 A g −1 and 90.2% capacitance retention even after 10 000 cycles at 5 A g −1 . These numerical results show that the supercapacitors based on coal-based carbon materials have great potential in high performance electrochemical energy storage.